The Sorghum (Sorghum bicolor) Brown Midrib 30 Gene Encodes a Chalcone Isomerase Required for Cell Wall Lignification - Tetreault, Hannah M.; Gries, Tammy; Liu, Sarah; Toy, John; Xin, Zhanguo; Vermerris, Wilfred; Ralph, John; Funnell-Harris, Deanna L.; Sattler, Scott E. (Frontiers in Plant Science, 2021)
In sorghum (Sorghum bicolor) and other C4 grasses, brown midrib (bmr) mutants have long been associated with plants impaired in their ability to synthesize lignin. The Bmr30 gene, identified using a bulk segregant analysis and next-generation sequencing, was determined to encode a chalcone isomerase. Two independent mutations within this gene confirmed that loss of its function was responsible for the brown leaf midrib phenotype and reduced lignin concentration. Loss of the Bmr30 gene function, as shown by histochemical staining of leaf midrib and stalk sections, resulted in altered cell wall composition. In the bmr30 mutants, chalcone isomerase activity was drastically reduced, and the accumulation of total flavonoids and total anthocyanins were impaired, which is consistent with its function in flavonoid biosynthesis. The level of the flavone lignin monomer tricin was reduced 20-fold in the stem relative to wild-type, and to undetectable levels in the leaf tissue of the mutants. The bmr30 mutant, therefore, harbors a mutation in a phenylpropanoid biosynthetic gene that is key to the interconnection between flavonoids and monolignols, both of which are utilized for lignin synthesis in the grasses.